Frequency of autoantibody formation in multi-transfused thalassemia patients at a tertiary care hospital: a cross-sectional study - Al-Mamun, A. B. M.; Islam, M. Ashadul; Fatema, Kaniz (International Journal of Research in Medical Sciences, 2024)
Background: Autoantibodies are produced by the immune system against the body’s own proteins, such as red blood cells, particularly after transfusions. This phenomenon, known as erythrocyte autoimmunization, has been a recognized complication of repeated transfusions. The purpose of this study was to evaluate the frequency of autoantibody formation in multi-transfused thalassemia patients at a tertiary care hospital. The aim of the study was to detect the frequency of autoantibody formation in multi-transfused thalassemia patients at a tertiary care hospital. Methods: This cross-sectional study at the department of transfusion medicine, BSMMU, Dhaka, conducted from October 2017 to September 2018, included 384 thalassemia patients who received at least 10 units of red cell concentrate. Informed consent was obtained, and data collection involved patient interviews, clinical exams, and hematological tests. Statistical analysis using SPSS version 23.0 included Chi-square, Fisher’s exact, and t-tests, with significance set at p<0.05. Results: In the study of 384 patients, 43.5% were under 10 years old, with a majority of 52.9% male. Coombs’ test showed 3.1% DCT positive, 7.5% ICT positive, and 4.2% positive for both. All 12 DCT-positive patients had a history of drug use, and 7.7% had undergone splenectomy. Conclusions: In conclusion, regular blood transfusion in thalassemia patients is a key factor in autoimmunization, with lower antibody formation in females, younger patients, and those with blood group B, while Rh phenotype-matched blood and prestorage leukodepletion may help reduce autoantibody formation.